Akulturasi Budaya Secara Verbal dan Kultural pada Upacara Tedhak Siten bagi Masyarakat Jawa - Dwi Wulandari (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
This study is aimed at examining the cultures acculturated in tedhak siten ceremony, a ceremony marking the early step of a baby toward walking conducted by Javanese people. This study is also describing the cultural behavior and cultural items used during the process of the ceremony. This article is a library study focusing on how earlier studies discuss the ceremony from different location in Java. The acculturation observed during tedhak siten ceremony is Javanese, Hindu, and Islam culture, and each of the culture has merged in through the process during years of its implementation. The acculturation can be seen on the cultural behavior and cultural items known as ubarampe in Javanese. This study is also taking a look at various symbols used during the process which all can lead to the thought and the hope for the baby to gave goodness in his/her life. The ceremony also implicitly shows how the Javanese as the parents of the baby play their roles as husband and wife, and therefore they are able to have good parenting skills for the baby. Kajian ini dilakukan untuk melihat budaya apa saja yang terakulturasi pada upacara tedhak siten atau upacara turun tanah bagi bayi yang dilakukan oleh masyarakat Jawa. Selain itu kajian ini juga mendeskripsikan perilaku budaya dan benda budaya yang digunakan dalam prosesi upacara tersebut. Kajian ini merupakan kajian pustaka yang mendasarkan pembahasannya dari temuan temuan kajian sebelumnya. Akulturasi budaya yang terlihat dalam prosesi tedhak siten adalah budaya Jawa, Hindu, dan Islam, yang masing masingnya melebur dengan baik selama proses puluhan tahun. Akulturasi tersebut terlihat pada perilaku budaya dan benda budaya yang berupa makanan dan uborampe upacara. Kajian ini juga mengungkap beragam simbol yang digunakan selama proses upacara yang semuanya dimuarakan pada satu hal yaitu harapan kebaikan bagi si anak. Upacara ini juga menyiratkan bagaimana hubungan dan peran orang tua Jawa sebagai suami istri yang nantinya akan mengasuh anak tersebut hingga bisa mencapai tujuan yang diharapkan.